Das Parlament der Dinge: Transmateriale und transmediale Dynamiken, Bild-Ding-Relationen und „Meta-Artefakt-Malerei“ - Schulz, Vera-Simone (Artium Quaestiones, 2019)
Studies related to artifacts, to what has been traditionally categorized as ‘high’ and ‘minor’ or ‘applied arts’, and to the materiality of art in recent years have been among the core foci of art history. More scholarly attention has also been given to the intersections between visual and material culture, not least in transcultural contexts. This paper seeks to contribute to these issues. Investigating transmaterial and transmedial dynamics between the arts, image-object interrelations as well as phenomena wherein images themselves gave the impulse to the creation of artifacts, the paper analyzes transfer processes transgressing various media and materials, 15th- and 16th-century Italian and Portuguese paintings in their Mediterranean and global entanglements, as well as 19th - and 20th-century artistic and academic approaches to objects in paintings.